DEVELOPING LEARNING MATERIALS OBJECTORIENTED PROGRAMMING COURSE BLENDED BASED IN THE COVID-19 PANDEMIC PERIOD - Maspaeni; Suyitno Muslim; Nurdin Ibrahim (Journal of Islamic, Social, Economics and Development, 2022)
One of the competencies that computer students need to have in creating applications using the concept of Object-Oriented Programming (OOP). The ability to make this application can be measured based on student learning outcomes from OOP courses. By looking at the final scores of all computer students at the Faculty of Information and Communication Technology (FICT) University of Technology Mataram (UTM) in the last three years, most of them scored below B, indicating that more than 50% of the students do not have the ability or not so understand about making applications with the OOP concept. Based on a good analysis of student needs, problems were found. Through various studies, research was conducted to develop learning materials to improve student learning outcomes of FICT UTM during the covid-19 pandemic. This research was conducted using the Research and Development (R&D) method by combining the steps developed by Borg & Gall, Dick & Carey, Rowntree, and Allan Jolliffe. Applying learning materials for OOP courses developed effectively could increase student learning outcomes by 50%. The effectiveness of this learning outcome was measured based on the results of testing the effectiveness of the product through the post-test with the result that 85% of students were declared complete in achieving the expected minimum competency standard with an average score of 80.40 when compared to the score through the pre-test which averaged 57.20 with the number of students who were declared complete by 35%.